DETERMINANTS OF DOMINANT MENTAL STATES OF ATO COMBATANTS - Ievdokimova, Olena (PSYCHOLOGICAL JOURNAL, 2018)
In the paper, the influence of a number of factors on the specificity of the dominant mental states of combatants was investigated. In the article the mental state is considered as an integral characteristic of a person’s mental activity for a certain period of time, showing the peculiarity of the course of mental processes depending on reflected objects and phenomena of reality, on the previous state and personality properties. The dominant mental state is considered as a condition that is characteristic not so much of a given particular moment, which depends on the characteristics of a particular situation, but much more in general for a certain period of a person’s life. The dominant mental state is less conditioned by the actual, current situation, has an accurately delineated time frame, and is largely determined by socio-psychological personal factors. On the background of the dominant states, actual states are formed and exist. Dominant states can be determined by many influences. The purpose of this work is to reveal the specifics of the dominant mental states of combatants, depending on such seemingly obvious, but, as it turned out, little studied factors like “was or was not the combatant under fire”, “was/was not treated in hospital”, “was / was not a witness of death”, “volunteer / mobilized”, “whether there were losses of friends during military service”, depending on the period of staying in the war zone, on marital status, on the availability of children, on the availability of employment before To determine the characteristics of the dominant mental states, the technique “Determination of dominant states” by L. Kulikov was used.. Mathematical and statistical analysis did not reveal significant differences in the indicators of dominant mental states between groups whose representatives were / were not under fire; between the groups formed according to the criterion of staying in the hospital; by the criterion of “loss of friends during military service”, by the criterion of having children. In the military group who observed death during military operations, on the scale “Satisfaction − dissatisfaction with life as a whole”, the figure was significantly higher than in the group of servicemen who were not witnesses of death. That is, combatants who survived the death of fighting friends, close people, found the ability to value life more in general, more satisfied with its current and opportunities for self-realization. An empirical study showed that of all the factors were studied, the greatest influence on the dominant mental states of servicemen has a “period of staying in the war zone” and anxiety connected with job in the pre-war period.